Technical Report Form - Building Livelihoods and Resilience to Climate Change in East and West Africa: Agricultural Research for Development (AR4D) for large-scale implementation of Climate-Smart Agriculture - Partnerships for Scaling Climate-Smart Agriculture (P4S) - Bayala, Jules (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Technical Report Form as part of the Building Livelihoods and Resilience to Climate Change in East and West Africa: Agricultural Research for Development (AR4D) for large-scale implementation of Climate-Smart Agriculture project / Partnerships for Scaling Climate-Smart Agriculture (P4S).